Edukasi Kesehatan Tentang Fluor Albus (Keputihan) Pada Ibu Hamil Dengan Service Excellent Education Di PMB Shinta Medan Polonia Tahun 2024 - Friza Novita Sari Situmorang; Yesica Geovany Sianipar; Rismalia Tarigan; Marshinta Sirait; Nadya Nabila; Irma Wati (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
Fluorus albus (vaginal discharge) is white fluid that comes out of the sexual canal in excess. Fluorus albus is a vaginal fluid, not blood. During pregnancy, vaginal discharge increases in quantity. According to the World Health Organization (WHO), recommendations in America that reproductive health problems include 31.6% of pregnant women experiencing vaginal discharge (fluor albus) caused by the fungus Candida albican. In Indonesia, the problem of vaginal discharge is increasing, with more than 75% of women experiencing vaginal discharge due to the humid temperature in Indonesia, making them easily infected. candida albicans fungus, parasites such as pinworms or germs (trichomonas vaginalis) (WHO, 2019). According to data from the 2019 North Sumatra Province Health Profile, there were 648,829 pregnant women in 2019, 1,566 cases of pregnant women experiencing vaginal discharge, in the city of Medan in 2019 there were 855,281 people and 45% had experienced vaginal discharge (North Sumatra Health Profile, 2020) . Method: This activity begins with the preparation, implementation and evaluation stages. Results: 15 participants in this activity were pregnant women who visited PMB Shinta in Medan Polonia, Medan City. In its implementation, it was explained that the genital organ problem that pregnant women often experience, especially in the third trimester, is fluoride albus (vaginal discharge). The types of vaginal discharge also need to be understood as well as the treatment and therapy that needs to be given to pregnant women in preventing and treating cases of Fluor Albus. Conclusion: The results obtained from this community service activity are an increase in knowledge about preventing vaginal discharge and the treatment that will be carried out if complications occur. Pregnant women who experience vaginal discharge will pose a risk to the health and growth and development of their fetus later. The risk of vaginal discharge before and after was an increase of 15% for the good level of knowledge, and 27% for the sufficient level, and at the level of poor knowledge it decreased by 40%. With this change in the level of knowledge and strengthening understanding of Fluor Albus, it is hoped that pregnant women will be more aware of the conditions of their pregnancy, especially in maintaining personal hygiene which will result in disruption of fetal growth and development. Conclusion: The results obtained from this community service activity are an increase in knowledge about preventing vaginal discharge and the treatment that will be carried out if complications occur. Pregnant women who experience vaginal discharge will pose a risk to the health and growth and development of their fetus later. The risk of vaginal discharge before and after was 15% increased for the good level of knowledge, and 27% for the sufficient level, and for the poor knowledge level it decreased by 40%.